A Localized Chimeric Hydrogel Therapy Combats Tumor Progression through Alteration of Sphingolipid Metabolism - Pal, Sanjay (ACS Cent Sci, 2019)
[Image: see text] Rapid proliferation of cancer cells assisted by endothelial cell-mediated angiogenesis and acquired inflammation at the tumor microenvironment (TME) lowers the success rate of chemotherapeutic regimens. Therefore, targeting these processes using localized delivery of a minimally toxic drug combination may be a promising strategy. Here, we present engineering of a biocompatible self-assembled lithocholic acid-dipeptide derived hydrogel (TRI-Gel) that can maintain sustained delivery of antiproliferating doxorubicin, antiangiogenic combretastatin-A4 and anti-inflammatory dexamethasone. Application of TRI-Gel therapy to a murine tumor model promotes enhanced apoptosis with a concurrent reduction in angiogenesis and inflammation, leading to effective abrogation of tumor proliferation and increased median survival with reduced drug resistance. In-depth RNA-sequencing analysis showed that TRI-Gel therapy induced transcriptome-wide alternative splicing of many genes responsible for oncogenic transformation including sphingolipid genes. We demonstrate that TRI-Gel therapy targets the reversal of a unique intron retention event in β-glucocerebrosidase 1 (Gba1), thereby increasing the availability of functional Gba1 protein. An enhanced Gba1 activity elevates ceramide levels responsible for apoptosis and decreases glucosylceramides to overcome drug resistance. Therefore, TRI-Gel therapy provides a unique system that affects the TME via post-transcriptional modulations of sphingolipid metabolic genes, thereby opening a new and rational approach to cancer therapy.